Analisis perkembangan Desa Kualan Hulu Kecamatan Simpang Hulu Kabupaten Ketapang Tahun 2014-2019 - V.K. Mareto Pissa; Suherdiyanto Suherdiyanto; Dian Equanti (LPD IKIP PGRI Pontianak, 2022)
This research is entitled â€œanalyze the development of the area in Kualan Hulu Village, Simpang Hulu District, Ketapang Regency in 2014 â€“ 2019â€. The purpose of this study is to analyze the development of the area in Kualan Hulu Village, Simpang Hulu District, Ketapang Regency in 2014 - 2019 and describe the socio-cultural development of the community in Kualan Hulu Village, Simpang Hulu District, Ketapang Regency in 2014-2019. This study uses a qualitative research approach where qualitative research as a scientific method is often used and carried out by a group of researchers in the social sciences, including education in a descriptive form. The results in this study are the development of the upstream village from 2014-2019 the development is so rapid and evenly distributed, because the community is very supportive of the village government so that it becomes an advanced and developing village for the sake of the future of students in the future who have more potential and have the spirit to build as expected. already exist now, because later it is very important for each individual to get facilities as a support or as a tool to achieve dreams in the hope that the development of advanced and developing villages helps the process in any way from an economic point of view for each individual and the community's economy continues to develop.